Geoheritage Sites and Geoconservation at Pha Chan - Sam Phan Bok Geopark, Ubon Ratchathani Province, Thailand - Vimoltip Singtuen; Krit Won-In (Geoconservation Research)
The Pha Chan - Sam Phan Bok Geopark is at the easternmost part of Thailand and has the border with Laos. Furthermore, it is the most famous Mekong River Civilization area and dominated by sedimentary rocks of the Khorat Plateau. Different erosion rate produces spectacular landforms such as potholes, rapids, stacks, cliffs, and cascades. According to inventory, characterization, classification and evaluation, these landforms are highly valuable elements to the regional heritage especially in the Pha Taem Cliff, which has outstanding prehistoric rock art. This research is demonstrating in different approaches to manage and present the geoheritage sites to tourists so that geological processes can be understood and geomorphological heritage preserved by the general public.